Pembangunan Aplikasi Pembelajaran Huruf Menggunakan Realiti Terimbuh - Rosman, Mohamad Roshaiqal Ameen; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2021)
Learning applications using augmented reality are now gaining more and more attention. However, most existing applications are less likely to allow users to interact with augmented reality objects. Also, the required markers are hard to come by and have to be paid for. A Learning Alphabets Using Augmented Reality project aims to develop a mobile application called ABC Realiti Terimbuh to make the alphabets learning more interactive and improve the existing application. The objectives of this project are to design ABC Realiti Terimbuh application using augmented reality, to develop ABC Realiti Terimbuh application using augmented reality and, on the Android, mobile platform and to test the application to target users which are children aged 4 to 6 years old. The methodology used for this project is Multimedia Mobile Content Development model. The developed application has three modules namely the Mengenal Huruf, Mari Mengeja and Kuiz. Usability testing was conducted for this application and showed a usability score among users of 87.67% using the System Usability Scale (SUS). Based on the result of usability score, this application is within the acceptable ranges. A future improvement for this application is to make it able to use marker-less augmented reality.